To solve this equation, you know you have two numbers which you can represent with x and y.
Larger number = y Twice the smaller number subtracted from the larger
Smaller number = x is equal to 13:
y - 2x = 13 Solve for y: y = 2x + 13 Then substitute your value for y into the equation they gave you at the beginning:
(2x + 13) + x = 52 Solve the equation by simplifying:
3x = 52 - 13 3x = 39 x = 13 Then substitute your value for x (13) into the equation we made to solve for y:
y - 2(13) = 13 y - 26 = 13 y = 39
So your answer is, "The two numbers are 13 and 39."